Spatial data, analysis, and regression - a mini course - Daniel Arribas-Bel (REGION, 2014)
This resource contains the materials and structure suggested to run a mini course of approximately 14 hours on spatial data, analysis and regression. The course is structured along four lectures and four labs that require the use of computers.
Keywords: 330; Spatial Analysis; course; open-source; Spatial Analysis; Spatial Econometrics; Methods